Peran Profitabilitas dalam Memoderasi Kebijakan Deviden dan Struktur Modal Terhadap Nilai Perusahaan: Bukti Negara Asean - Fitriyanthi, Dini; Luthan, Elvira (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
ASEAN is one of the fastest growing regions in the world in 2023, but economic growth in this country is likely to decline compared to 2022. This is due to the worsening global economic conditions and monetary policy. This economic growth often has a negative impact on the value of the company, so efforts are needed that can support the company's value to be achieved optimally, one of which is by analyzing the dividend policy and capital structure factors in influencing the firm's value. This study aims to analyze and provide empirical evidence of the influence of dividend policy and capital structure on firm value with profitability as a moderation. This study uses secondary data in the form of financial reports of ASEAN companies listed on the Stock Exchange based on Refinitiv Eikon for 2019-2023. The population of this study is all ASEAN countries, the sample obtained is 2,071 data, 727 companies from 6 ASEAN countries. The results of this study prove that (1) dividend policy has a significant negative effect on firm value (2) capital structure does not have an effect on firm value (3) profitability does not moderate dividend policy on firm value (4) profitability moderates capital structure on firm value. The results of this study provide important insights for companies and investors in making decisions regarding dividend policy and capital structure. Companies need to carefully consider factors such as investment opportunities, profitability, and risk before determining dividend policy and capital structure. Investors also need to conduct a careful analysis of these factors before making investment decisions.